An extended winding function model for induction machine modelling considering saturation effect. Issue 1 (13th December 2020) - Gholami, Mehrdad; Shahryari, Om‐Kolsoom; Tarimoradi, Hadi
Abstract: Winding function (WF) method is one of the electric machines modelling methods, which is used to simulate electric machines under different conditions. It has less simulation time and memory than other methods and, at the same time, has comparable accuracy over other methods. One of the significant challenges of WF‐based models is how to model saturation. The accuracy of the fault detection method in electric machines depends on the accuracy of the model and the method used for the simulation. A new extended model of the WF is presented for saturation modelling, which considers all parts of the core including teeth, slots, and yokes. In this method, the effect of the iron parts is emulated as a partial value that is added to the length of the actual air gap. The simulation results for normal and faulty conditions are shown in two cases, with and without considering saturation effect. Then the importance of saturation modelling has been demonstrated. Simulation is done in MATLAB software. Moreover, the experimental results are shown to verify the proposed model.